PENGARUH MOTIVASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT SIANTAR TOP TANJUNG MORAWA - Rosniwaty Bangun; Riama Ines Clara (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2021)
This study aimed to determine the effect of motivation and compensation on employee job satisfaction at PT Siantar Top Tanjung Morawa. The population of this study is all employees at PT Siantar Top Tanjung Morawa and the sample is a population of 85 people. The method used to obtain data is by distributing questionnaires/questionnaires. The data analysis technique used is multiple linear regression analysis technique at a significance level of = 0.05. The results showed that the significant value of each variable was below 0.05, namely 0.22 and 0.03. This states that there is a significant influence between motivation and work compensation on employee performance variables. The results of the F test obtained a significant value of 0.000 <0.05. This states that simultaneously the variables of motivation and work compensation have a significant effect on performance. Furthermore, the results of the coefficient of determination obtained an RSquare value of 0.771, which means that variations in employee performance variables can be explained by motivation and work compensation as much as 77.10%. The remaining 22.90% were influenced by other things outside the research focus.